How Fair Is Income Taxation in the View of the German Public? - Jürgen Schupp; Gert G. Wagner (Weekly Report, 2005)
It is not possible to provide a scientific answer to questions regarding the 'fairness' of taxation. Nonetheless, empirical economics and social science research can still yield helpful information for legislators charged with deciding on the level and structure of the tax system. Such research also includes the public's assessment of the fairness of the tax system. At the beginning of 2005, DIW Berlin incorporated questions concerning the fairness of income taxation in its 'Socio-Economic Panel' longitudinal study. Preliminary findings of this research are now available. The tax burden on unskilled workers was considered excessively high by almost two-thirds of respondents. By contrast, the burden on the board members of large enterprises was considered too low by three-quarters of those surveyed, and this view was actually shared by two-thirds of the executive staff in the sample. However, it is not possible to draw any direct conclusions for economic and fiscal policy from these findings. The evaluation of such data is a wholly political act lying in the exclusive domain of the parliament. However, these results at least demonstrate unambiguously that when it comes to the issue of income and fiscal equity, people belonging to all sections of the population think in a more egalitarian manner than is assumed by large segments of public opinion and politics.
Keywords: 330